(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Essay Prompt: In his publication “Principles of Inner Work: Psychological and Spiritual,” John Welwood coined the term “spiritual bypass.” This concept is described in the accompanying passage. It can refer to using faith or religion to avoid the reality of difficult or intense emotions. Did any of the patients that were interviewed display this psychological defense? Can you think of an example from the media or your personal experiences where this process was at play? In the space below, please 1) briefly describe one example of spiritual bypass from one of these sources, and 2) discuss how spiritual bypass may be harmful or helpful depending on the situation.